2009
DOI: 10.1111/j.1469-8986.2008.00776.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular reactivity to psychological stress and carotid intima‐media thickness in children

Abstract: The relationship between cardiovascular stress reactivity and carotid artery intima-media thickness (IMT) has been established in adults, but not yet studied in children. Cardiovascular reactivity to an ad lib speech was measured in 20 boys and 20 girls age 11.0 +/- 1.4 years. Measures included heart rate (HR), systolic (SBP) and diastolic (DBP) blood pressure reactivity, and mean common carotid artery IMT. Sequential regression analyses were used to establish the incremental increase in R(2) for the predictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 65 publications
5
26
1
1
Order By: Relevance
“…These results replicate previous research that stress-induced SBP reactivity to preparing and then given an interpersonal speech is associated with subclinical cardiovascular disease in children. 10 Moreover, the present study extends earlier work by demonstrating that an aggregate stress reactivity measure that provides a more reliable reflection of ‘trait’. cardiovascular reactivity, 13 predicts greater intima-media thickness.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These results replicate previous research that stress-induced SBP reactivity to preparing and then given an interpersonal speech is associated with subclinical cardiovascular disease in children. 10 Moreover, the present study extends earlier work by demonstrating that an aggregate stress reactivity measure that provides a more reliable reflection of ‘trait’. cardiovascular reactivity, 13 predicts greater intima-media thickness.…”
Section: Discussionsupporting
confidence: 85%
“…9 Until recently the relationships between psychological stress-induced cardiovascular reactivity and intima-media thickness had not been investigated in youth. Roemmich and colleagues 10 presented initial evidence that systolic blood pressure (SBP) reactivity, but not diastolic BP (DBP) or heart rate (HR) reactivity, was associated with carotid artery intima-media thickness in children. A more recent study found that children who displayed greater DBP reactivity increases over the course of 3 years exhibited greater intima-media thickness.…”
Section: Introductionmentioning
confidence: 99%
“…One has reliably associated suboptimal nocturnal sleep with increased cardiovascular morbidity and mortality and total mortality [5,6,22,23] while the other has reliably established cardiovascular reactivity and recovery as a risk factor for cardiovascular morbidity [7][8][9][10]17]. By allotting participants an interval for daytime sleep and assessing same-day cardiovascular response, we were able to create a situation where daytime sleep could be quantitatively assessed for its recuperative and protective cardiovascular benefits.…”
Section: Resultsmentioning
confidence: 96%
“…For example, nocturnal sleep length has been associated with increased risk of pre-hypertension and hypertension in adolescents [5] and adults [6]. A separate literature implicates exaggerated cardiovascular reactivity to psychological stress in the laboratory [7] with increased risk for cardiovascular disease in adolescents [8] and adults [9]. Further, recent longitudinal studies suggested that blunted post-stress blood pressure recovery was associated with increased risk of acute myocardial infarction [10], carotid intima-media thickening [11], and hypertension [12].…”
Section: Introductionmentioning
confidence: 93%
“…As noted above, some individuals have a reliable tendency to express relatively large rises in blood pressure that are viewed to exceed the metabolic demands of a given stressor (Obrist, 1981). Indeed, this exaggerated cardiovascular response tendency appears to be a trait-like dispositional characteristic of some individuals (Allen et al, 1987; Cohen and Hamrick, 2003; Fauvel et al, 1996; Gerin et al, 1993; Kamarck et al, 1994; Kamarck and Lovallo, 2003; Llabre et al, 1991; Manuck et al, 1995a; Sherwood et al, 1990), which may be partially heritable (De Geus et al, 2007; Turner and Hewitt, 1992) and predictive of atherosclerotic and CHD risk early in development (Matthews et al, 2006; Roemmich et al, 2009). Moreover, individuals expressing exaggerated stressor-evoked cardiovascular reactions, particularly exaggerated blood pressure reactions, appear to be at elevated risk for precursors to CHD and related endpoints in later life.…”
Section: Stressor-evoked Blood Pressure Reactivity and Chd Risk: Epidmentioning
confidence: 99%